Incorporating silica nanoparticles with silver patches into alginate-based bioinks for 3D bioprinting - Anspach, Annalise; Bider, Faina; Völkl, Andreas; Klupp Taylor, Robin; Boccaccini, Aldo R. (MRS Communications, 2024)
Alginate dialdehyde-gelatin (ADA-GEL) hydrogels are being studied in bioprinting for their combination of cell adhesion and printability. To incorporate specific functionalities and to improve printability, different additives to ADA-GEL inks are being proposed. Here, a novel type of functional nanoparticles comprising silver patches on silica cores was incorporated into ADA-GEL bioinks. Silver patchy particles (SPPs) were present both on the surface and interior of printed structures. Incorporation of SPPs improved printability of ADA-GEL inks and supported osteosarcoma (MG-63) cells over 7 days of culture. SPPs represent a valuable additive for ADA-GEL hydrogels, being attractive to develop bioinks with advanced functionalitie